Intervention and assessment of executive dysfunction in patients with stroke: A scoping review. - Katsuya Sakai; Yuichiro Hosoi; Junpei Tanabe (PLoS ONE)
Rehabilitation methods for executive dysfunction were focused on cognitive rehabilitation in patients with stroke and traumatic brain injury. However, no reviews have focused on the various rehabilitation methods and assessment of executive function in patients with only stroke and included various study designs. This study aimed to identify various interventions and assessments in patients with stroke and executive dysfunction via a scoping review. We searched for articles using the PubMed, Web of Science, and CINAHL databases. Two reviewers independently screened the articles based on the inclusion and exclusion criteria using the title, abstract, and full text. We subsequently determined the study design, sample size, time since stroke, intervention, and assessment. We extracted 1131 articles, of which 27 articles were selected. The study designs were randomized controlled trials (81.5%), pilot studies (11.1%), and feasibility studies (7.4%), with a total of 599 participants. Interventions varied from cognitive training (22.2%), virtual reality (22.2%), noninvasive brain stimulation (14.8%), and dual-task training (11.1%), with consistent results. The assessments used were the Trail Making Test Part B (70.4%), Stroop Color and Word Test (44.4%), Digit Symbol Test, Frontal Assessment Battery, and Tower of London test (11.1%). In conclusion, this scoping review provided various interventions and assessments in patients with stroke with executive dysfunction.